Education Transdisipliners: Integration Interconnection Approach in Independent Curriculum Policy Learning-Independent Campus - Sonia, Nur Rahmi (Proceeding International Conference on Religion, Science and Education, 2022)
This article discusses the concept of the integration-interconnection-transdisciplinary approach in the study of the Independent Learning Campus (MBKM) education policy. It is known that the demands, needs and currents of changing times are getting faster. Universities are required to be able to design and implement innovative learning processes so that students can achieve learning outcomes that include aspects of attitudes, knowledge, and skills optimally. In the MBKM curriculum there is a student exchange program that provides students with the opportunity to deepen their scientific fields that are not found in the Study Program. The research method used is library research, to develop the concept of an integrated-interconnective-transdisciplinary approach in the MB-KM curriculum, researchers explore various literature from relevant articles and books. The results of the literature study explain that to deal with complex conditions, it is necessary to reform the university curriculum so that students have the ability to solve problems with various scientific disciplines and are able to adapt to the world of work. The essence of MBKM is a student exchange program that facilitates students to be able to take knowledge from other scientific fields that they have never studied so that students can think flexibly and comprehensively. In addition to equipping with multidisciplinary or transdisciplinary scientific concepts, the student exchange program also provides provisions and character planting to recognize ethnicity, nation, culture, race and religion, thereby strengthening the essence of the value of unity and integrity and becoming a moderate nation. Thus, cross-disciplinary science changes a new paradigm that every scientific field has the opportunity to be collaborated with other sciences through the MBKM curriculum.